2023
DOI: 10.54012/jcell.v2i4.137
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Verbal Linguistic Intelligence and Reading the Qur'an in an Islamic Perspective

Abstract: The reality that still occurs among students is that they cannot read the Qur'an fluently. It is not surprising that there are students who respond slowly in learning the Qur'an. This study aims to determine the accuracy between verbal-linguistic intelligence and reading the Qur'an. The authors use a theoretical descriptive method with content analysis techniques by quoting several opinions according to experts and according to an Islamic perspective. The discussion results show that students with verbal-lingu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…This study was limited during its implementation due to the needs of standardized test to measure students' verbal aptitude. Meanwhile, some other studies successfully revealed the significant correlation between verbal aptitude and reading comprehension (Schroeder, 2011;Trassi et al, 2019;Gumiandari, et al, 2023). On the other hand, Ratnasari (2016) also conducted similar study on verbal aptitude but at the age of elementary school.…”
Section: Introductionmentioning
confidence: 90%
“…This study was limited during its implementation due to the needs of standardized test to measure students' verbal aptitude. Meanwhile, some other studies successfully revealed the significant correlation between verbal aptitude and reading comprehension (Schroeder, 2011;Trassi et al, 2019;Gumiandari, et al, 2023). On the other hand, Ratnasari (2016) also conducted similar study on verbal aptitude but at the age of elementary school.…”
Section: Introductionmentioning
confidence: 90%